Service-learning in design and planning : educating at the boundaries - Angotti, Thomas, 1941-; Doble, Cheryl S.; Horrigan, Paula (New Village Press, 2011)
"This collection of case studies by design educators critically explores the current practice of community-engaged learning in architecture, landscape design, and urban planning, radically revising the standard protocol for university-initiated design/build projects in the community. The editors' lively examination of real-life community alliances forms a pedagogical framework for design educators, offering guidelines for a generative and inclusive collaborative design process. Includes contributions by the leading practitioners of service-learning in the design professions, including Daniel Winterbottom, Peilei Fan, and Michael Rios"--